Numerical Simulation and Design of Improved Optimized Green Advertising Framework for Sustainability through Eco-Centric Computation - Mahato, Mrinal Kanti; Seth, Salil; Yadav, Parveen (International Journal of Intelligent Systems and Applications in Engineering, 2023)
The umbrella concept of sustainability encompasses multi-dimensional philosophies like monetary, eco-centric and resource-oriented philosophies. Keeping in view the alarming eco-concerns across the globe, the eco-centric philosophy of sustainability has taken a centre- stage for both marketers and consumers. Green Advertising as a competitive weapon of marketers reverberates closely with sustainable consumption of goods in consonance with remarkable stewardship towards the ecological environment. This conceptual paper with a novel environment-oriented approach to sustainability attempts to qualitatively justify the nexus between Green Advertising & Sustainability by suggesting a construct post-application of grounded theory embedded conceptual framework analysis. The exploratory research design bases itself on secondary data sources entailing journals from management as well environmental sciences. The inter-disciplinary approach of the paper makes it valuable for policy drafters of Sustainability Development Goals (SDGs), environmental strategists, social advocates of Green Advertising and opinion leaders who are willing to transcribe all anthropogenic interventions in the direction of eco-centrism.